Ts. ChM Dr. Ahmad Zamani invents DECO2X, a catalyst to convert carbon dioxide into methane - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (UMPSA, 2023)
GAMBANG, 19 December 2023 - Energy-to-product technology (Power to X) is the best technology that uses renewable energy sources such as solar or wind energy to convert carbon dioxide combined with hydrogen into other products such as methane, methanol and others.